A weight of evidence assessment of the genotoxic potential of 4-methylimidazole as a possible mode of action for the formation of lung tumors in exposed mice. (November 2020) - Brusick, David; Aardema, Marilyn J.; Allaben, William T.; Kirkland, David J.; Williams, Gary; Llewellyn, G. Craig; Parker, Julia M.; Rihner, Marisa O.
Abstract: 4-Methylimidazole (4-MeI) is a byproduct formed during the cooking of foods containing carbohydrates and amino acids, including the production of flavors and coloring substances, e.g., class III and IV caramel colors, used in many food products with extensive human exposure. Two-year rodent bioassays via oral exposure conducted by the National Toxicology Program reported evidence of carcinogenicity only in B6C3F1 mice (increased alveolar/bronchial neoplasms). In 2011, the International Agency for Research on Cancer classified 4-MeI as Group 2B, "possibly carcinogenic to humans". An expert panel was commissioned to assess the genotoxic potential of 4-MeI and the plausibility of a genotoxic mode of action in the formation of lung tumors in mice when exposed to high doses of 4-MeI. The panel defined and used a weight-of-evidence (WOE) approach that included thorough evaluation of studies assessing the genotoxic potential of 4-MeI. The panelists categorized each study, consisting of study weight, degree of technical performance, study reliability, and contribution to the overall WOE. Based on the reviewed studies' weighted contribution, the panel unanimously concluded that the WOE supports no clear evidence of in vivo genotoxicity of 4-MeI and no association for a genotoxic mode of action in the formation of mouse lung tumors. Highlights: An expert panel assessed the genotoxic potential of 4-methylimidazole (4-MeI). The panel used a weight-of-evidence (WOE) approach for 4-MeI study evaluation. The expert panel evaluated study reliability and contribution to the overall WOE. The expert panel found no clear evidence of in vivo genotoxicity of 4-MeI. Genotoxic mode of action for mouse lung tumor formation is not plausible for 4-MeI.